Corporate board structure and foreign equity investments in weak institutional regimes. (19th August 2019) - Banerjee, Sujata; Oriani, Raffaele; Peruffo, Enzo
Abstract: Research Question/Issue: Concentrated ownership is more the rule than the exception in weak institutional environments, and the absence of external control mechanisms, leading to ineffective legal enforcement, intensifies principal–principal agency issues. Our study examines how the structuring of the corporate board plays a vital role in informing foreign investors about the risk of being expropriated, which affects their decisions to make equity investments in firms in weak institutional regimes. Research Findings/Insights: Using a sample of large listed Indian firms in the period 2010–2014, we hypothesize that the presence of affiliate directors on the board has a negative impact on foreign investments. Likewise, the presence of controlling owners‐directors on the board together with chief executive officers' additional directorial positions has an inverted U‐shaped impact on foreign investments. Theoretical/Academic Implications: By making use of agency theory and focusing on the importance of foreign financing, our study highlighted the factors that deter foreign investors from providing capital to firms in weak institutional regimes. The use of this theoretical perspective, by emphasizing the differences in agency problems prevalent in strong versus weak institutional regimes, further suggested that examination of the structure of corporate boards is an important way to detect and gauge the potential for expropriation in countries suffering from weaknesses in investor protection. Practitioner/Policy Implications: Our study has important implications for corporations operating in markets suffering from a legal environment that offers little investor protection. Investors are less prone to invest in these countries, as the risk of expropriation by dominant shareholders means they cannot be sure of actually getting the putative return. Our work shows how corporations can structure their boards effectively to convince investors that they face less danger of expropriation and so attract foreign capital.